No associations between HIV reservoir and inflammation in long-term virally suppressed dolutegravir-based ART-treated individuals - Fombellida-Lopez, Céline; Aguilar Ortmans, Diego; Moutschen, Michel; Pasternak, Alexander O.; Darcis, Gilles (Frontiers in Immunology, 2025)
IntroductionDespite effective antiretroviral therapy (ART), people with HIV (PWH) experience persistent immune activation and inflammation, increasing the risk of non-AIDS-related comorbidities. The contribution of the HIV reservoir to this chronic inflammatory state remains debated. Understanding the relationship between HIV persistence, immune activation, and inflammation is crucial for optimizing long-term therapeutic strategies.MethodsThis study assessed HIV persistence, immune activation, and systemic inflammation in 49 PWH treated with the same dolutegravir-based triple ART regimen. HIV reservoir size and activity were evaluated by measuring total HIV DNA in peripheral blood mononuclear cells (PBMCs) and rectal tissue, cell-associated (CA) unspliced (US) HIV RNA, and residual viremia. Over 20 inflammatory biomarkers, including sCD14, IL-6, TNF-α, and CXCL10, were analyzed, along with comprehensive immune profiling using a 26-color spectral flow cytometry panel. Clinical parameters such as age, nadir CD4 count, and co-infections were also considered.Results and discussionOur findings showed a limited association between HIV persistence markers and systemic inflammation or immune activation. Compared to previous studies, participants had lower reservoir sizes and transcriptional activity, likely due to early ART initiation and prolonged suppression. Immune preservation was evident, with high CD4/CD8 ratios and reduced activation markers. These results challenge the idea that the HIV reservoir is the primary driver of chronic inflammation in PWH on a dolutegravir-based long-term ART. Instead, the reservoir may evolve toward a more transcriptionally silent and defective state, reducing its impact on systemic immune activation.